Democratizing Risk Governance (Springer Nature, 2023)
This open access book features contributions from a multidisciplinary team of leading and emerging scholars focused on democratization of risk assessment, management, and communication. The volume identifies and sheds light on key risk governance dilemmas related to public trust, risk perception and public participation. The first part of the book articulates the relationship among science, expertise, deliberation and public values, featuring an in-depth analysis of the concept of ‘motivated reasoning,’ and the role of trust, values and worldviews in understanding and addressing contemporary controversies over risk decision-making. The volume’s second part features eight case studies from three policy fields – energy, genomics, and public health – and a special section dedicated to vaccine decision-making for Covid-19. Chapters analyze the level, nature and mechanisms of public involvement in risk decision-making, assessing its contribution to the effectiveness and legitimacy of decisions. The case studies focus predominantly on Canada, but they draw on global scholarship and are of direct relevance for scholars and practitioners of risk governance in any country.